Hydrology a science for engineers - Hingray, Benoît (CRC Press, 2015)
This book presents the main hydrological methods and techniques used in the design and operation of hydraulic projects and the management of water resources and associated natural risks. It covers the key topics of water resources engineering, from the estimation of runoff volumes and unit hydrographs to the routing of flows along a river and through lakes, reservoirs, and hydraulic structures. It deals with questions regarding basic hydrological data, hydrological modeling and the prediction and forecasting of low flows and flood discharges.
Keywords: Hydrology.; Water resources development.; elektronické knihy; electronic books